Behavior of the solutions of certain systems of non-integer differential equations - Ben Othmane Iman; Nisse Lamine (University Of Eloued جامعة الوادي, 2020)
This work is devoted to the generalization of certain theorems of comparisons known in the theory of ordinary differential equations,to systems of differential equations of fractional order.
comparison and principle of the maximum
Intervention
Keywords: Fractional integral; Riemann-Liouville derivative; Caputo derivative; fractional differential system; differential inequality; integral inequality; comparison theorems